Chemical profiling, in vitro antioxidant, membrane stabilizing and antimicrobial properties of wild growing Murraya paniculata from Amarkantak (M.P.) - Shruti Sonter (Nature Portfolio, 2021)
Abstract The excessive usage of antibiotics in humans and veterinary medicine has lead to the emergence of antibiotic resistance and now requires the use of novel antibiotics. There has been increased interest towards plants as source of drugs because of their pharmacological potency and long traditional usage. The aim of the current study was to evaluate bioactive components, antioxidant, and anti-inflammatory activities of the leaf extracts of Murraya paniculata, a plant traditionally used in Indian medicinal system. Evaluations were made for phytochemical analysis, antioxidant, membrane stabilizing, and antimicrobial activities. The methanol extract displayed the highest flavonoid and phenolic content, the acetone extract demonstrated considerable ABTS inhibitory activity (IC50value:555.18 ± 1.68 µg/mL) and the hexane extract exhibited highest H2O2 radical scavenging activity (IC50value: 509.84 ± 3.03 µg/mL). The aqueous extract displayed 19.4 ± 0.66% RBC hemolysis and 80.5 ± 0.66% protection caused by hypotonic solution at high concentration of the extract. The fractions of hexane extract revealed a higher zone of inhibition than crude extract. The major components found in the fractions were cyclohexane (40.11%) and 3-(6-Methoxy-3-methyl-2-benzofuranyl) Cyclohexanone (13.68%) as analyzed by GC–MS/MS technique. The current results validate the traditional use of the M. paniculata and warrant its potential in drug development programs in further investigations.